Effectiveness of a Transitional Care Support Program for People with Heart Failure: A Randomized Controlled Trial. - Sunonnam, Ratchaneekorn; Siripitayakunkit, Apinya; Jianvitayakij, Soontaree (Pacific Rim International Journal of Nursing Research)
Heart failure is a chronic condition that impacts the health, well-being, and quality of life of people with heart failure. Living with heart failure requires consistent and effective self-care for preventing rehospitalization. Research on transitional care interventions that integrate evidence-based practice is limited, and its combined impact justif ies further rigorous investigation. This randomized controlled trial aimed to examine the effects of a transitional care support program on self-care behavior, quality of life, and hospital readmission in people with heart failure at a tertiary hospital in northeastern Thailand. Sixty-six participants were randomly assigned to the experimental group (n = 33) and the comparison group (n = 33) using a computer-generated simple randomization sequence. The experimental group received a four-week Transitional Care Support Program developed by the researchers, in addition to usual care, while those in the comparison group received only usual care. Data were collected at three time points: baseline, immediately post-intervention (week 4), and eight weeks after the program ended (week 12), using the Demographic and Health Record Form, the Self-Care of Heart Failure Index, and the Minnesota Living with Heart Failure Questionnaire. Data were analyzed using descriptive statistics, a mixed-design repeated measures analysis of variance, and the Chi-square test. The results revealed that the experimental group had signif icantly higher self-care behavior and quality of life than the comparison group. Furthermore, the experimental group had a signif icantly lower number of hospital readmissions within 28 days after discharge than the comparison group. Advanced practice nurses can play a vital role in implementing this program for people with heart failure during the transition from hospital to home. However, further testing with a larger sample size and in various settings is needed before the program can be widely adopted.